Potensi air leri sebagai Pupuk Organik Cair (POC) dalam pertumbuhan tanaman pakcoy: Review jurnal - Nisa, Amalia Wizarotun (Maliki Interdisciplinary Journal, 2024)
Rice washing water is one of the alternatives for food crop farmers in reducing the use of chemical fertilizers. The nutrient content contained in rise washing water can provide sufficient nutrients to stimulate plant growth, especially pakcoy. Pakcoy plants are vegetable commodities that have good production. This research was conducted with a qualitative method, namely comparig references from several scientific journals that conduct independent research on similar problems that have been done. The result of this research is that it is known that the fermenting water combined with AB mix produced pakcoy plants are superior compared to ferry water which is only diluted with water using different concentrations.